2004
DOI: 10.1097/01.asn.0000140219.28618.9f
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Erythropoietin Antibody-Mediated Pure Red Cell Aplasia after Treatment with Recombinant Erythropoietin Products

Abstract: Abstract. Since 1998, there has been a marked increase in incidence of pure red cell aplasia secondary to development of anti-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 19 publications
2
40
0
1
Order By: Relevance
“…There are reports of PRCA caused by formulations other than EPREX®: 0.02-0.16 per 10,000 patients for subcutaneous administration and 0.02 per 10,000 patients for intravenous administration [189]. Patients with PRCA were reported following the administration of epoetin-α and epoetin-β, which are commercially available in Japan, although the number of such patients was extremely small [190][191][192].…”
Section: Prcamentioning
confidence: 99%
“…There are reports of PRCA caused by formulations other than EPREX®: 0.02-0.16 per 10,000 patients for subcutaneous administration and 0.02 per 10,000 patients for intravenous administration [189]. Patients with PRCA were reported following the administration of epoetin-α and epoetin-β, which are commercially available in Japan, although the number of such patients was extremely small [190][191][192].…”
Section: Prcamentioning
confidence: 99%
“…For NSF, reports of a gadodiamide-NSF relationship from Austria and Denmark were published three months apart and for PRCA, reports from the United States/Europe and Canada were published on the same day. 5,43,50,51 For RS, a preliminary report of the Arizona case-control study in the Morbidity and Mortality Weekly Report in July 1980 was followed by preliminary and final reports of Michigan and Ohio studies with similar findings six and 18 months later, respectively. 22-25 Regulatory responses were delayed and uncoordinated.…”
Section: Discussionmentioning
confidence: 99%
“…Independently, Cournoyer et al reported subcutaneous administration of epoetin alfa with polysorbate 80 had the highest PRCA incidence rates. 50 In 2005, the groups collaboratively reported that epoetinassociated PRCA disappeared following renal transplantation. 51 In 2009, epoetin-associated PRCA resolved in 13 of 14 patients who received a novel peptide-based erythropoietin-receptor agonist.…”
Section: Pure Red Cell Aplasiamentioning
confidence: 99%
See 1 more Smart Citation
“…The development of anti-EPO antibodies is a very rare but serious complication of treatment with erythropoietic agents. From 1998 to 2004, it was apparent that there was a significant increase in the number of patients who developed pure red-cell aplasia (PRCA) secondary to the appearance of neutralizing anti-EPO antibodies [76,77] . PRCA is characterized by severe anemia, high transfusion requirement and a total lack of response to increasing doses of rHuEPO.…”
Section: Side Effects Of Esasmentioning
confidence: 99%